Effectiveness of a Group Educational Program on the Knowledge, Attitude, and Participation Approach of Mothers in the Sex Education of Preschool Children - H Fatehi Pouladi; M Akbari Kamrani; M Javad Noori; M Farid (Iran University of Medical Sciences, 2019)
Background & Aims: Parents, especially mothers, play a pivotal role in the sex education of children; therefore, justification of children regarding sex education by the parents is considered essential. The present study aimed to assess the effectiveness of a group educational program on the knowledge, attitude, and participation approach of mothers in the sex education of preschool children. Materials & Methods: This randomized, controlled, parallel clinical trial was conducted on 58 mothers with children aged 3-7 years employed at Alborz University of Medical Sciences in Karaj, Iran during May-September 2018.  The participants were randomly allocated to the intervention and control groups via drawing lots. Data were collected using a demographic form and researcher-made questionnaire with three sections on maternal knowledge, attitude, and participation in the sex education of preschool children. The participants in the intervention group received three training sessions (90 minutes each) and provided with an instruction booklet. The questionnaire was completed before and one month after the intervention. Data analysis was performed in SPSS version 19. Results: The results of Mann-Whitney U test indicated a significant difference between the intervention and control groups in terms of the mean score of maternal knowledge of the sex education of children after the educational program (P=0.007). In addition, the results of independent t-test denoted a significant difference in the mean score of maternal attitude between the intervention and control groups after the training (P=0.007). The results of paired t-test also showed a significant difference in the mean score of maternal participation approach in the two groups before and after the intervention as the score increased after the educational program (P=0.0001; t(24)=8.440).  Conclusion: According to the results, the mothers reported more participation in the sex education of their children after the educational intervention. Therefore, it is recommended that seminars, workshops, and counseling sessions be provided for parents, as well as caregivers in child care centers.